Anterior cruciate ligament injuries in soccer: Loading mechanisms, risk factors, and prevention programs - Dai, B.; Mao, D.; Garrett, W. E.; Yu, B. (Journal of Sport and Health Science, 2014)
Anterior cruciate ligament (ACL) injuries are common in soccer. Understanding ACL loading mechanisms and risk factors for ACL injury is critical for designing effective prevention programs. The purpose of this review is to summarize the relevant literature on ACL loading mechanisms, ACL injury risk factors, and current ACL injury prevention programs for soccer players. Literature has shown that tibial anterior translation due to shear force at the proximal end of tibia is the primary ACL loading mechanism. No evidence has been found showing that knee valgus moment is the primary ACL loading mechanism. ACL loading mechanisms are largely ignored in previous studies on risk factors for ACL injury. Identified risk factors have little connections to ACL loading mechanisms. The results of studies on ACL injury prevention programs for soccer players are inconsistent. Current ACL injury prevention programs for soccer players are clinically ineffective due to low compliance. Future studies are urgently needed to identify risk factors for ACL injury in soccer that are connected to ACL loading mechanisms and have cause-and-effect relationships with injury rate, and to develop new prevention programs to improve compliance